PrPc deficiency and dasatinib protect mouse intestines against radiation injury by inhibiting of c-Src. Issue 1 (July 2016) - Strup-Perrot, Carine; Vozenin, Marie-Catherine; Monceau, Virginie; Pouzoulet, Frederic; Petit, Benoit; Holler, Valérie; Perrot, Sébastien; Desquibert, Loïc; Fouquet, Stéphane; Souquere, Sylvie; Pierron, Gérard; Rousset, Monique; et al.
Abstract: Background & Aim: Despite extensive study of the contribution of cell death and apoptosis to radiation-induced acute intestinal injury, our knowledge of the signaling mechanisms involved in epithelial barrier dysfunction remains inadequate. Because PrP c plays a key role in intestinal homeostasis by renewing epithelia, we sought to study its role in epithelial barrier function after irradiation. Design: Histology, morphometry and plasma FD-4 levels were used to examine ileal architecture, wound healing, and intestinal leakage in PrP c -deficient (KO) and wild-type (WT) mice after total-body irradiation. Impairment of the PrP c Src pathway after irradiation was explored by immunofluorescence and confocal microscopy, with Caco-2/Tc7 cells. Lastly, dasatinib treatment was used to switch off the Src pathway in vitro and in vivo . Results: The decrease in radiation-induced lethality, improved intestinal wound healing, and reduced intestinal leakage promoted by PrP c deficiency demonstrate its involvement in acute intestinal damage. Irradiation of Cacao2/Tc7 cells induced PrP c to target the nuclei associated with Src activation. Finally, the protective effect triggered by dasatinib confirmed Src involvement in radiation-induced acute intestinal toxicity. Conclusion: Our data are the first to show a role for the PrP c -Src pathway in acute intestinal response to radiation injury and offer a novel therapeutic opportunity.